2018
DOI: 10.4025/enfoque.v37i2.34035
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Sistema Financeiro Na Evidenciação Socioambiental De Empresas Em Países Emergentes E Desenvolvidos

Abstract: RESUMOO estudo avalia a influência do sistema financeiro da Austrália, do Brasil, do Canadá e da Índia sobre a extensão da divulgação de informações de responsabilidade social corporativa (RSC) de empresas de setores ambientalmente sensíveis. Para esse fim, foram selecionadas empresas dos setores de utilidade pública, materiais básicos e de operações de petróleo e gás presentes na lista da Forbes 2000 do ano de 2008. A pesquisa é quantitativa e o período analisado compreendeu os anos de 2007 a 2014. A variável… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 5 publications
(5 reference statements)
4
10
0
11
Order By: Relevance
“…For the general sample, a positive and significant effect of ease of access to credit was found on CSP and environmental disclosure, although the regression coefficient is low. These findings converge with the findings from previous studies, such as Soares et al (2018) and Soares et al (2020). According to Baldini et al (2018), economic freedom and ease of financing for companies can reduce the effects of corruption and encourage companies to take responsibility for their environmental impacts.…”
Section: Regesupporting
confidence: 93%
“…For the general sample, a positive and significant effect of ease of access to credit was found on CSP and environmental disclosure, although the regression coefficient is low. These findings converge with the findings from previous studies, such as Soares et al (2018) and Soares et al (2020). According to Baldini et al (2018), economic freedom and ease of financing for companies can reduce the effects of corruption and encourage companies to take responsibility for their environmental impacts.…”
Section: Regesupporting
confidence: 93%
“…These results can be explained by the reason that emerging markets have high levels of corruption, but their companies tend to have a greater social and environmental disclosure, in order to get more foreign investments, since the financial system of these markets tend to be fragile. Soares et al (2018) found that Brazilian and Indian companies carry out greater social disclosure than Australian and Canadian companies.…”
Section: Discussionmentioning
confidence: 99%
“…Este resultado corrobora com os trabalhos de Abreu et al, (2015) e Soares et al (2018) que confirmam a influência do ambiente institucional do Brasil nas práticas de RSC. Países em desenvolvimento, possuem limites turvos nos SNN, e usam a evidenciação como um meio para facilitar a captação de recursos financeiros.…”
Section: Discussionunclassified
“…Os autores mostram que, de modo geral, as variáveis no nível da firma são os principais determinantes para a extensão de RSC das empresas. Nesse sentido, Soares et al (2018) sugerem que as características do sistema financeiro são determinantes na evidenciação em países emergentes, quando comparadas a empresas em países desenvolvidos…”
Section: Discussionunclassified